Long-term Evaluation of Residual Viremia in a Clinical Trial of Dolutegravir Plus Lamivudine as Maintenance Treatment for Participants With and Without Prior Lamivudine Resistance. (8th November 2022) - De Miguel Buckley, Rosa; Rial-Crestelo, David; Montejano, Rocío; Pinto, Adriana; Jimenez-Gonzalez, María; Lagarde, Maria; Esteban-Cantos, Andrés; Aranguren-Rivas, Paula; Cadiñanos, Julen; Bisbal, Otilia; Castro, Juan Miguel; Santacreu-Guerrero, Mireia; et al.
Abstract: In this pilot clinical trial, we evaluated rates of residual replication in persons without lamivudine resistance-associated mutations in proviral DNA population sequencing who switched to dolutegravir plus lamivudine. After 144 weeks, there was no signal of changes in residual viremia based on qualitative detection methods, irrespective of past lamivudine resistance. Clinical Trials Registration. NCT03539224.